2021
DOI: 10.3390/ani11020351
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Cowsheds in Vietnamese Smallholder Dairy Farms and Their Associations with Microclimate—A Preliminary Study

Abstract: In smallholder dairy farms (SDFs), farmers often build cowsheds using local materials and based on self-accumulated experience without due consideration to reducing the risk of heat stress. This study aimed to characterise the heat stress abatement strategies and microclimate within SDF cowsheds from four typical dairy regions of Vietnam (south lowland, south highland, north lowland and north highland) and identify the housing parameters most associated with the microclimate. The study was conducted on 32 SDFs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 32 publications
2
11
0
Order By: Relevance
“…30 Several relatively low-cost relief strategies are effective and profitable in reducing heat stress impacts, including the use of simple sheds that are well-designed for providing shade, bathing animals several times each day, and installing electric fans in sheds. 31 Different arrangements of shade trees in treelivestock systems can be highly effective in reducing heat stress. 32 For more intensive cattle production systems in which animals are confined or confined seasonally, there are many alternative cooling, ventilation, and buildingdesign options.…”
Section: Discussionmentioning
confidence: 99%
“…30 Several relatively low-cost relief strategies are effective and profitable in reducing heat stress impacts, including the use of simple sheds that are well-designed for providing shade, bathing animals several times each day, and installing electric fans in sheds. 31 Different arrangements of shade trees in treelivestock systems can be highly effective in reducing heat stress. 32 For more intensive cattle production systems in which animals are confined or confined seasonally, there are many alternative cooling, ventilation, and buildingdesign options.…”
Section: Discussionmentioning
confidence: 99%
“…In lower input livestock systems, various lower cost adaptation strategies may be effective in reducing the impacts of heat stress in smallholder systems. These include the use of simple sheds to provide shade, animal baths, roof soaking, and installing fans in sheds, for example (Bang et al, 2021 ; York et al, 2017 ). Certain arrangements of shade trees in silvopastoral livestock production systems, particularly in Latin America, have been shown to be an effective means of reducing heat stress (Cuartas Cardona et al, 2014 ; Ibrahim et al, 2006 ; Pezzopane et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, eight SDFs per region were randomly selected from the SDFs in that economic survey who agreed to continued involvement in further studies. More details about the process to select the SDFs for the current study can be found in our previous studies (Bang et al, 2021c , 2021b , 2021a, 2021d).…”
Section: Methodsmentioning
confidence: 99%
“…Microclimate data from 0600 to 1800 h within the cowshed of each SDF was measured by a Kestrel 5400 Heat Stress Tracker (NIELSEN-KELLERMAN, USA). Means (± SD) of ambient temperature, humidity, and temperature-humidity index (THI) in South Lowland were 29.5 ± 1.1°C, 81.8 ± 3.8%, and 82.5 ± 1.3 units, respectively; in South Highland, 25.4 ± 1.3°C, 80.5 ± 4.9%, and 75.5 ± 1.6 units; in North Lowland, 29.7 ± 1.5°C, 82.0 ± 6.0%, and 82.9 ± 2.0 units; and in North Highland, 26.0 ± 1.1°C; 80.6 ± 4.1%, and 76.7 ± 1.3 units (Bang et al, 2021c ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation